The Meaning of Kant’s Attitude Towards the Technical Instruments of Science in the Atmosphere of Enlightenment - Ana BAZAC (Studia Universitatis Babeș-Bolyai. Philosophia)
I mention the main, technophile and technophobe, positions towards technology in the Western 18th century, as the criterion of this paper. Then I show that, however unexpected would this be, the concept of technics – opening the problem of technics – was explicitly present within the transcendental philosophy. From its multiple meanings outlined in the logic of this philosophy, I focus on the technical instruments of science. Kant considered them optimistically, but insisted that they are only means subordinated to the capability of reason that alone is able to give knowledge. And the vault key of knowledge is the moral law (the moral telos) given by the human reason. Thus, answering to Rousseau, Kant indicates that the progress of knowledge is ultimately determined by this moral, and not by the enrichment of cognisance as a result of technical instruments. If we consider them as a model for the treatment of the technical objects in the broad sense of this term, Kant introduced the criticism of the technophile reductionism, while creating the frame of the positivist science and the humanistic philosophy of the 19th century.